2015
DOI: 10.1111/bjd.14037
|View full text |Cite
|
Sign up to set email alerts
|

Canakinumab in adults with steroid‐refractory pyoderma gangrenosum

Abstract: SummaryBackground Pyoderma gangrenosum (PG) is a rare, neutrophilic, ulcerative skin disease that is difficult to treat, especially when unresponsive to steroids. Objectives To determine whether canakinumab is an effective and safe treatment in PG. Methods Five adult patients with clinically and histologically confirmed steroidrefractory PG were enrolled in this prospective open-label study. They received canakinumab 150 mg subcutaneously at week 0 with an optional 150 mg at week 2 in case of an inadequate res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 40 publications
0
88
0
7
Order By: Relevance
“…PG is frequently associated with systemic diseases. Increased expression of IL-1β was found in lesional skin of PG patients compared to healthy skin (Marzano et al, 2014b; Kolios et al, 2015). In an open-label, proof of concept study evaluating the anti-IL-1β monoclonal antibody Gevokizumab, six patients with active ulcers received three subcutaneous injections once every 4 weeks and four out of six patients had a complete clearance of the target ulcer, 1 a partial (90%) closure of the ulcer and 1 did not respond (ClinicalTrials.gov Identifier: NCT01882504) (Huang et al, 2014, poster).…”
Section: Skin Diseases With Il-1 Involvementmentioning
confidence: 94%
See 1 more Smart Citation
“…PG is frequently associated with systemic diseases. Increased expression of IL-1β was found in lesional skin of PG patients compared to healthy skin (Marzano et al, 2014b; Kolios et al, 2015). In an open-label, proof of concept study evaluating the anti-IL-1β monoclonal antibody Gevokizumab, six patients with active ulcers received three subcutaneous injections once every 4 weeks and four out of six patients had a complete clearance of the target ulcer, 1 a partial (90%) closure of the ulcer and 1 did not respond (ClinicalTrials.gov Identifier: NCT01882504) (Huang et al, 2014, poster).…”
Section: Skin Diseases With Il-1 Involvementmentioning
confidence: 94%
“…In an open-label study, five steroid-refractory PG patients were treated with Canakinumab once with 150 mg at onset and then optionally at weeks 2 and 8 if response was suboptimal. At the week 16 study endpoint 80% of the patients showed decreased size of target ulcers and 60% were in complete remission (ClinicalTrials.gov Identifier: NCT01302795) (Kolios et al, 2015). A case report described complete healing of a PG patient that received a Canakinumab monthly at a 150 mg dose for 3 months (Galimberti et al, 2016).…”
Section: Skin Diseases With Il-1 Involvementmentioning
confidence: 99%
“…With regard to systemic drugs, steroids were the mainstay of treatment; second choices were cyclosporine and dapsone. Following the recent expansion on the use of biological drugs, 15.6% of patients have been treated with anti‐TNFα with good results, but further studies and trials must be performed before considering these drugs (included IL‐1 antagonist and IL‐12/23) the first choice in treating PG. Finally, Japanese authors report the use of granulocyte and monocyte adsorption apheresis (GCAP) to treat steroid‐resistant PG, but we have no experience with such therapies.…”
Section: Discussionmentioning
confidence: 99%
“…As the PSTPIP1 gene is associated with the inflammasome pathway, IL‐1β blockade has been a successful therapy for PAPA syndrome. Recently, isolated pyoderma gangrenosum was also found to have increased IL‐1β and was treated successfully in an investigator‐initiated trial with anti‐IL‐1β blockade, resulting in an 80% response rate …”
Section: Associated Conditions and Overlap Conditionsmentioning
confidence: 99%